Academic performance and standardized departmental tests: A study in higher education - Gutiérrez Benítez, Jorge Gustavo; Casillas Domínguez, José Manuel; Olguin Jiménez, Karina (IE Revista de Investigación Educativa de la REDIECH, 2024)
Educational institutions are increasingly required to pursue results that demonstrate the quality of their processes, which is why they choose to apply standardized assessment methods and procedures to contribute to achieve such requirements. The present work analyzes the psychometric quality and the results obtained in terms of academic performance of standardized departmental tests for the two subjects of greatest curricular relevance of the common core of languages in the School of Languages at the Universidad Autónoma de Baja California, analyzing mainly three factors of influence in them. Variance analyses, correlational analyses, and independent sample tests were used on a sample of 1,025 students who answered the test from 2017 to 2023. A satisfactory average level of academic performance was observed for one test while a deficient one for the other, and the teacher was identified as the main influencing factor in academic performance, followed by the format of application of the test. The results show a higher-than-standard psychometric quality in the tests, pointing out the importance of establishing a teacher training program as well as structuring an approved teaching-learning process but flexible enough to result in improving performance in the departmental test for all students.